Dynamic Response of Buried Silo Caused by Underground Explosion - Sylwester Kobielak; Theodor Krauthammer (Shock and Vibration)
Experimental results of normal and tangential pressures on a buried silo wall caused by buried charge explosions are presented in the paper. The measured pressures depended on the charge mass, and its burial depth and distance from the silo front. Pressures were measured by sensors attached to the silo wall at different depths along to four diametrically opposite line generators located at the front, rear and two sides. The influence of each parameter is analyzed and discussed.